Characterization protection method for ring block friction pair transfer film

By using a three-layer composite structure back-type protective tape to protect the ring block friction pair transfer film, the pollution problem during the cutting process is solved, and the effective protection of the transfer film and the accuracy of subsequent analysis is achieved.

CN119643241AActive Publication Date: 2025-03-18WUHAN RES INST OF MATERIALS PROTECTION
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411688549.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively protect the ring block friction pair transfer film, especially during the cutting process, which is susceptible to contamination by cutting fluid, affecting the accuracy of subsequent characterization and analysis.

Method used

The back-type protective tape protective ring sample with a three-layer composite structure is adopted, including a protective layer, a functional layer and a viscous layer. The functional layer material is adjusted according to the working conditions of the test environment. The inner area of ​​the viscous layer covers the area to be analyzed, and the outer area is in contact with the end face of the ring sample.

Benefits of technology

It effectively avoids the pollution of the transfer film by cutting fluid, ensures the structural integrity of the transfer film and the accuracy of the composition analysis, and is suitable for ring sample protection under various working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643241A_ABST
    Figure CN119643241A_ABST
Patent Text Reader

Abstract

The invention discloses a characterization protection method for a ring block friction pair transfer film, and belongs to the technical field of friction testing. According to the method, by using the concentric-square-shaped protective adhesive tape, the transfer film on the surface of the friction pair material is effectively protected, pollution of cutting fluid to the surface in the cutting process is avoided, and the structural integrity of the transfer film and component and bonding structure analysis of the transfer film are ensured. According to different test environment working conditions, the thickness and the material of the second functional layer are adjusted and optimized, so that the original state of the to-be-analyzed area of the ring sample after the friction test under different test environment working conditions can be effectively maintained, and the subsequent characterization analysis result is more accurate; and the friction and wear mechanism of the ring block under different working conditions can be analyzed more deeply. The method is easy to operate, economical in cost and suitable for protecting transfer films of ring samples of various sizes and various working conditions, and the transfer films can be effectively protected on the premise that the accuracy of a frictional wear characterization result is not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of friction testing, and in particular to a characterization and protection method for a transfer film of a ring-block friction pair. Background Art

[0002] Friction pair refers to the part where friction and wear occur between the surfaces of objects in relative motion. Suitable friction pair materials can slow down the wear process, extend the life of parts and reduce maintenance costs. During the friction process, the wear debris generated by the wear of polymer materials will be transferred to the metal surface, and a thin film will be generated through a series of physical and chemical reactions. This film is called a transfer film. In tribology research, the ring-block friction test is a commonly used test method, which is widely used to evaluate the friction and wear properties of materials during rotational motion. In order to deeply analyze the friction and wear mechanism, it is necessary to characterize the composition and structure of the transfer film attached to the worn surface of the ring sample (i.e., the circumference of the ring sample) in detail, such as using scanning electron microscope (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and other methods. However, these characterization techniques have strict requirements on sample size. For example, some models of XRD analysis chambers require that the sample height does not exceed 15 mm, while the diameter of the ring sample in the friction test is usually not less than 50 mm, so it is impossible to conduct direct testing and it is difficult to directly place the ring sample into the XRD analysis chamber for analysis and characterization.

[0003] In order to solve this problem, operators usually need to cut the ring sample to meet the size requirements of the instrument. During the cutting process, wire cutting technology is often used. Wire cutting technology uses the principle of local melting of metal by electric sparks. Although it can achieve high-precision cutting, coolant (cutting fluid) is required during the cutting process to prevent overheating. However, the transfer film is usually thin and fragile, and is easily damaged by external forces or environmental factors. In addition, the cutting fluid used usually has a complex chemical composition and a certain solubility, which may cause the transfer film to dissolve or peel off, thereby affecting the fixation effect of the transfer film produced on the surface of the ring sample. The composition of the cutting fluid is complex and contains a variety of organic solvents. If the transfer film attached to the peripheral surface of the ring sample is not protected and the wire cutting process is performed directly, the sample surface may be contaminated, thereby affecting the accuracy of subsequent characterization. In actual operation, technicians usually choose to cover the surface of the ring sample with tape to block contamination. However, this method is relatively primitive and it is difficult to fully protect the structural integrity of the transfer film. In addition, in friction testing, the test environment conditions are constantly changing, and a single protection method is increasingly difficult to meet the test requirements under various application conditions. The above technical problems restrict the analysis of the composition and bonding structure of the transfer film, as well as a more in-depth analysis of the friction and wear mechanism of the ring block under different working conditions.

[0004] Therefore, how to effectively protect the circumference of the ring sample from contamination by the wire cutting fluid while cutting the ring sample so that the final characterization test results can truly reflect the element types and friction chemical mechanism of the ring sample surface after wear has become a technical problem in tribology research. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a characterization and protection method for the transfer film of the ring-block friction pair with strong protection and wide application is provided, comprising the following steps: During the cutting process of the ring sample, the ring block friction pair transfer film of the ring sample is protected by a return-shaped protective tape; The protective tape includes a three-layer composite structure, which is a protective layer, a functional layer and an adhesive layer. The functional layer is a functional tape whose thickness and material are adjusted according to the test environment conditions; The viscous layer includes an inner area and an outer area; the outer area is a viscous glue, which is fixed to the end faces of both sides of the ring sample by its viscosity; the inner area is a groove area without viscous glue in the viscous layer, covering the wear surface to be analyzed in the transfer film of the ring-block friction pair.

[0006] The material selection of the protective layer is diverse, and materials with protective and isolating effects on the coolant can be used, such as waterproof tape, etc. The position of the inner area in the adhesive layer can be adjusted accordingly, and those skilled in the art can determine its appropriate size, shape and distribution according to the actual range of the protected surface.

[0007] Preferably, the test environment conditions include seawater environment, low speed and low load, and high temperature environment.

[0008] Further preferably, when the test environment is a seawater environment, the seawater concentration is divided into low concentration, medium concentration and high concentration; the low concentration simulates natural seawater, and its NaCl concentration is lower than 3.5 wt.%; the medium concentration simulates a high-salinity sea area, and its NaCl concentration is 3.5 wt.%-5.0 wt.%; the high concentration simulates an extreme salt water environment, and its NaCl concentration is higher than 5.0 wt.%; The thickness of the functional layer is 2.0-3.5 mm, and its material components include a resin matrix, a water absorbent and a chloride ion absorbent.

[0009] Furthermore, under low-concentration seawater conditions, the mass ratio of the resin matrix, the water absorbent and the chloride ion absorbent is 88-92:5:3-7; under medium-concentration seawater conditions, the mass ratio of the resin matrix, the water absorbent and the chloride ion absorbent is 83-87:5:8-12; under high-concentration seawater conditions, the mass ratio of the resin matrix, the water absorbent and the chloride ion absorbent is 78-82:5:13-17.

[0010] Ordinary protective measures are difficult to meet the test requirements of seawater environment, and they mainly face the following technical problems: 1. Ionic pollution: The ionic components in seawater (Cl - etc.) may react with the sample material, causing changes in the chemical composition of the transfer film surface and affecting subsequent characterization and analysis results; 2. Hydrate formation: In an environment with high humidity, additional hydrates may form on the surface of the friction specimen, affecting the judgment of the friction characteristics and wear behavior of the actual ring-block friction pair material.

[0011] Therefore, the present invention changes the ratio of the chloride ion absorbent in the functional layer material according to the different concentrations of seawater salt ions in the friction test to avoid residual Cl - Degradation of transfer film. Use moisture absorbent to avoid high humidity environment inside the protective tape.

[0012] Furthermore, the resin matrix includes one of polyurethane, epoxy resin, and polyvinylidene fluoride; the water absorbent includes one of sodium polyacrylate, polyvinyl alcohol, and cellulose derivatives; and the chloride ion absorbent includes one of hydroxide-type strong base anion exchange resin, quaternary ammonium cationic adsorption resin, and zinc oxide nanoparticles.

[0013] Further preferably, when the test environment working condition is low speed and low load, the speed of low speed and low load is 0-100 rpm, the load is 0-50 N, and the thickness of the functional layer is 0.5-1.5 mm.

[0014] When the friction working condition of the ring-block friction pair is low speed and low load, due to the low speed and low load friction conditions, the generated transfer film is usually thin (thickness within a few microns). When the thickness of the functional layer is too large, it will cause stress concentration in the weak area of ​​the transfer film, thereby causing the transfer film to be damaged. Therefore, based on the test application requirements of the present invention, the thickness of the functional layer should be controlled within the range of 0.5-1.5 mm. The present invention avoids applying excessive pressure to the weak area of ​​the transfer film to damage the transfer film by regulating the optimal thickness of the functional layer. It should be noted that this parameter is determined according to the specific design process of the inventor, and is not a conventional choice for non-technical personnel: Through experiments, the inventors measured the thickness of the transfer film under different friction conditions. For example, when the speed was 50 rpm and the load was 20 N, the average thickness of the transfer film was X μm, while when the speed was 100 rpm and the load was 50 N, the average thickness was Y μm. Then, using linear regression analysis, the relationship between the transfer film thickness and the functional layer thickness was established, which is in the form of T transfer = k × T function + b, where T transfer is the thickness of the transfer film, T function is the thickness of the functional layer, k and b are parameters to be determined.

[0015] When analyzing the effect of pressure, the formula P = F / A is used to calculate the pressure, where P is the pressure acting on the transfer film, F is the applied force, and A is the contact area. The contact area can be calculated from the diameter of the ring (d) and the thickness of the functional layer, specifically A = π × d × T function , from which the corresponding contact area can be calculated according to the thickness of the functional layer. In terms of the quantification of softness, Shore A is selected as the evaluation standard to record the hardness values ​​of different materials and relate them to the performance under low speed and low load conditions, using the formula Softness Index = 1 / H shore To quantify the softness of a material.

[0016] When performing pressure analysis, ensure that the pressure in the weak area does not exceed the index parameter (less than 50 kPa) applied in the present invention. The inventors have thus determined the optimal thickness range of the functional layer, thereby ensuring the stability of the transfer film under low speed and low load conditions. Those skilled in the art can also complete further thickness design under the guidance of this design process.

[0017] Further preferably, when the test environment is a high temperature environment, when the temperature is 150-300°C, the material of the functional layer 025 includes one of polyimide, polyetheretherketone, and phenolic resin-based composite materials; when the temperature is 300-1000°C, the material of the functional layer 025 includes one of ceramic fiber, alumina fiber, and silicon carbide fiber.

[0018] When the friction working condition of the ring-block friction pair is a high temperature environment, if the friction product is characterized immediately before the temperature of the friction pair cools down, the physical and chemical state of the material under high temperature conditions can usually be observed more closely in real time, and the microscopic morphology and chemical composition of the friction product are more likely to remain in the "original" state. When characterized after cooling, the oxides, thermal decomposition products, and transfer film surface microstructures change during the cooling process, and the temperature drop may cause oxidation or structural shrinkage, which will lead to deviations in the characterization analysis results. During the cooling process, a new oxide layer may form on the surface, or the microscopic morphology may change due to the release of thermal stress, thus affecting the accurate evaluation of the material's true friction behavior.

[0019] In high temperature environment conditions, the functional layer material of the present invention is designed as a heat insulation layer to reduce the impact of a sharp drop in temperature on the structure of the friction product. The function of the heat insulation layer is to maintain the temperature of the friction surface, reduce the speed of heat conduction during the cooling process, thereby delaying the changes in morphology or chemical composition caused by cooling, helping to preserve the state of the friction product at high temperature and reducing the difference in characteristics before and after cooling.

[0020] Preferably, a bending line is provided at the bending portion where the outer area is in fixed contact with the end surfaces on both sides of the ring sample.

[0021] The setting of the bending line enables the tape to fit better at the corner bend of the ring sample, thereby enhancing its adhesive performance, improving its flexibility and adaptability, and preventing the tape from loosening or peeling off at the bend.

[0022] Preferably, the operation process of the characterization and protection method for the transfer film of the ring-block friction pair in the friction test includes the following steps: (1) Install the ring specimen and the block specimen in the fixture of the experimental device respectively, and start the friction test according to the preset friction test conditions, including speed, load, temperature and time parameters; (2) After the friction test, take out the ring sample; observe the transfer film on its worn surface and determine the area to be analyzed; the area to be analyzed is the part where the surface morphology and state after the friction test are significantly different from those of the unworn area, which is convenient for further characterization and analysis of the friction and wear mechanism; (3) Align the inner area of ​​the adhesive layer of the protective tape with the area to be analyzed of the ring sample, so that the inner area covers the wear surface to be analyzed in the transfer film of the ring-block friction pair, and the outer area adheres to the end surfaces on both sides of the ring sample to complete the fixation, preventing the protective tape from shifting during the cutting process; (4) Perform wire cutting along the outer contour of the circular protective tape. After completion, take out the small ring sample obtained by cutting, clean the residual contaminants, and dry it for further testing; (5) Before characterization testing, remove the protective tape covering the small ring specimen and then conduct characterization testing.

[0023] Preferably, in step (5), the characterization test includes scanning electron microscopy analysis, X-ray diffraction analysis, energy dispersive spectrometry (EDS), and X-ray photoelectron spectroscopy analysis.

[0024] Based on the above technical scheme, the method of the present invention effectively protects the transfer film on the surface of the friction pair material by using a circular protective tape, avoids the surface contamination caused by the cutting fluid during the cutting process, and ensures the structural integrity of the transfer film and the composition and bonding structure analysis of the transfer film. According to different test environment conditions, the present invention can effectively maintain the original state of the area to be analyzed of the ring sample after the friction test under different test environment conditions by adjusting and optimizing the thickness and material of the second functional layer, so that the results of subsequent characterization and analysis are more accurate, which is helpful for a more in-depth analysis of the friction and wear mechanism of the ring block under different working conditions. The method is simple to operate and cost-effective. It is suitable for the transfer film protection of ring samples of various sizes and various working conditions, and can achieve effective protection of the transfer film without affecting the accuracy of the friction and wear characterization results.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a characterization and protection method for a transfer film of a ring-block friction pair, which has the advantages of strong protection and wide applicability, and improves the accuracy of tribology research. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the circular protective tape; Figure 2 This is a schematic diagram of the explosion of the circular protective tape; Figure 3 It is a top view of the area to be analyzed in the protective ring sample of the protective tape; Figure 4 It is an overall schematic diagram of the circular protective tape bonding ring specimen; Figure 5 It is a front view of the sample of the circular protective tape bonding ring; Figure 6 It is a side view of the circular protective tape bonding ring specimen; Figure 7 The SEM and EDS distribution of the wear surface of the 45 steel ring in seawater environment when the protective tape is not used; Figure 8 The SEM and EDS distribution of the wear surface of 45 steel ring in seawater environment when using the circular protective tape; Figure numerals: 01 - ring sample; 02 - circular protective tape; 021 - inner area; 022 - outer area; 023 - bending line; 024 - area to be analyzed; 025 - functional layer; 026 - protective layer. DETAILED DESCRIPTION

[0027] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0028] Example 1 The structure of the protective tape used in this embodiment is as follows: Figure 1 , 2 As shown. The circular protective tape 02 is a three-layer composite structure, which includes a protective layer 026, a functional layer 025 and an adhesive layer. The protective layer 026 is a waterproof tape; the functional layer 025 is a functional tape whose thickness and material are adjusted according to the test environment conditions. This embodiment is a common test condition. Those skilled in the art can select the appropriate material and thickness according to the actual test requirements. The adhesive layer is divided into an inner area 021 and an outer area 022. The outer area 022 is provided with a bending line 023 at the bending part where the end surfaces of both sides of the ring sample 01 are in contact and fixed, which helps to optimize the fitting effect of the bent part. The inner area 021 is a groove area without adhesive glue in the adhesive layer, and the outer area 022 is adhesive glue, which is fixed to the ring sample 01 by its adhesiveness.

[0029] The characterization and protection method for the transfer film of the ring-block friction pair in this embodiment uses a ring sample with a diameter of 55 mm. The experiment requires EDS analysis of the friction and wear surface of the ring sample to evaluate the element changes on the wear surface. The specific steps are as follows: (1) Fix the ring sample 01 and the block sample in the fixture of the friction tester respectively, and perform friction test at a rotation speed of 300 rpm and a normal load of 100 N. The friction time is set to 60 min. (2) After the friction test, the ring sample 01 was taken out and the wear condition on the surface of the ring sample 01 was observed. It was found that there were obvious friction marks on the sample. Through preliminary optical microscope observation, an outer area of ​​the ring sample 01 was determined to be the area to be analyzed 024; (3) Use tweezers to remove the protective tape 02. Figure 3 As shown, the center of the inner area 021 is aligned with the area to be analyzed 024, so that the whole is attached to the surface of the ring sample 01, and the outer area 022 is adhered to the end surfaces of both sides of the ring sample 01 to complete the fixation, ensuring that the friction surface is completely covered. The schematic diagram after fixation is shown in Figure 4-6 As shown; (4) Fix the ring sample 01 on the wire cutting machine and cut along the outer contour of the circular protective tape 02. Since the circular protective tape 02 effectively isolates the cleaning fluid, no contamination occurs during the cutting process. After cutting, rinse the sample surface with deionized water to remove residual cleaning fluid and impurities, and then dry the sample for further testing. (5) After removing the waterproof tape, XPS was used to analyze the element valence state of the sample surface. It was found that the valence state and distribution of the surface elements were consistent with the wear conditions under actual dry friction conditions and were not affected by the additional chemical elements contained in the cleaning fluid during the cutting process.

[0030] Example 2 The protective tape used in this embodiment is basically the same as that in embodiment 1, except that the components of the functional layer 025 in this embodiment are polyurethane, sodium acrylate, and hydroxide-type strong base anion exchange resin, with a mass ratio of 90:5:5. In the test, those skilled in the art can flexibly select the specific components and proportions of the corresponding functional layer 025 according to the concentrations and corresponding parameters divided by the present invention according to the test requirements of the seawater environment conditions.

[0031] This example is aimed at the characterization and protection method of the transfer film of the ring sample in the marine environment, and studies the friction performance of the ring sample in the seawater environment and high load conditions. The experimental environment is to simulate the marine conditions, the friction pair material is the marine coating material, and the ring sample and the block pair material are used in the experimental process. After the test, the surface of the sample is characterized and analyzed. The specific steps are as follows: (1) The friction test equipment was set to a normal temperature of 25 °C and a normal load of 500 N. A standard ratio seawater solution was used to simulate the marine environment. The ring specimen 01 and the block specimen were fixed in the fixture of the friction tester respectively. The friction test was carried out under the set seawater and high load conditions for 60 min. (2) After the friction test, take out the ring sample 01, and use a hair dryer to dry the seawater adsorbed on its surface until the surface is dry; use an optical microscope to observe the surface wear of the ring sample 01, and find that the wear is more obvious under high load conditions. The area with larger wear marks on the ring sample is determined to be the area to be analyzed 024; (3) Use tweezers to take out the circular protective tape 02 that fits the sample size, align the center of the inner area 021 with the area to be analyzed 024, and make it stick to the surface of the ring sample 01 as a whole. The outer area 022 is adhered to the two side surfaces of the ring sample 01 to complete the fixation, ensuring that the friction surface is completely covered; (4) Fix the ring sample 01 on the wire cutting machine and cut along the outer contour of the circular protective tape 02. After cutting, rinse the sample surface with deionized water to remove residual cleaning fluid and impurities, and then dry the sample for further testing; (5) After removing the waterproof tape, the cut sample pieces were analyzed using EDS. The results showed that the friction surface was not contaminated. Figure 7 The figure shows the SEM and EDS distribution of the wear surface of the 45 steel ring in the seawater environment when the protective tape is not used; Figure 8 The SEM and EDS distribution of the wear surface of the 45 steel ring in the seawater environment after the use of the protective tape. From the comparison of the two figures, it can be seen that when the protective tape is not used, the P, S and other elements contained in the cutting fluid contaminate the surface of the 45 steel ring sample. After the protective tape is used, it effectively prevents the intrusion of the cutting fluid, and there are no contaminating elements such as P and S. The analysis results accurately reflect the friction and wear of the material.

[0032] This example proves that the method of the present invention can effectively avoid the contamination of the transfer film on the surface of the worn ring sample in the marine environment by the cutting fluid during the wire cutting process, thereby ensuring the accuracy of the subsequent characterization analysis.

[0033] Example 3 The protective tape used in this embodiment is basically the same as that in embodiment 1, except that the thickness of the functional layer 025 in this embodiment is controlled within the design range corresponding to the low speed and low load condition. In this embodiment, the sample is subjected to friction test at room temperature, mainly to study the wear behavior and surface characteristics under low friction speed (low speed and low load), and the specific steps are as follows: (1) Fix the ring specimen 01 with a diameter of 60 mm and the corresponding block specimen on the friction tester, set the speed to 50 rpm, the normal load to 50 N, and perform the friction test at 25 °C for 60 min. (2) After the friction is completed, the surface of the ring sample 01 is observed through a microscope, and a portion with obvious difference between the friction area and the unworn area is selected as the area to be analyzed 024; (3) Use tweezers to take out the circular protective tape 02, align the center of its inner area 021 with the area to be analyzed 024, and stick it on the surface of the ring sample to ensure that the friction surface is completely covered; (4) Use a wire cutting machine to cut the ring sample 01 along the contour of the circular protective tape 02, and ensure that the cutting fluid does not contact the wear area; after cutting, use deionized water to clean the surface of the sample, and then dry it for later use; (5) After removing the protective tape, the phase composition of the sample surface was analyzed using XRD. The results showed that the friction surface was not contaminated by the cutting fluid and the test results were accurate.

[0034] This example demonstrates that under low speed and low load conditions, the method of the present invention can effectively isolate the contamination of the cutting fluid, so that the subsequent XRD characterization analysis has a high degree of reliability.

[0035] Example 4 The protective tape used in this embodiment is basically the same as that in embodiment 1, with the only difference being that the functional layer 025 in this embodiment is polyimide (polyetheretherketone and phenolic resin-based composite materials can also achieve the purpose of this embodiment. When the temperature is higher, technicians can choose ceramic fiber, alumina fiber, silicon carbide fiber) to meet the test requirements of high-temperature environment conditions. This embodiment studies the wear behavior and surface characteristics of the ring sample under high temperature environment and high load. The specific steps are as follows: (1) Install the ring sample 01 and the block sample with a diameter of 55 mm in the fixture of the high temperature friction tester respectively; set the friction speed to 200 rpm, the normal load to 500 N, and the temperature to 250 °C, and perform the friction test for 60 min; (2) After the friction test, take out the ring sample 01, observe the transfer film on its worn surface, and select the area with severe wear as the area to be analyzed 024. (3) Use tweezers to take out the circular protective tape 02, align the center of its inner area 021 with the area to be analyzed 024, and stick it on the surface of the ring sample 01 to ensure that the friction surface is completely covered; (4) Use a wire cutting machine to cut the ring sample 01 along the contour of the circular protective tape 02, and ensure that the cutting fluid does not contact the wear area; after cutting, use deionized water to clean the surface of the sample, and then dry it for later use; (5) The surface morphology of the cut specimens was analyzed using SEM. The results showed that the worn surface was not contaminated and the surface structure was clear.

[0036] This example demonstrates that the protective measures are still effective under high temperature and high load conditions, ensuring the integrity and cleanliness of the sample surface, and the characterization results truly reflect the high-temperature wear behavior of the material.

[0037] In summary, the characterization and protection method for the transfer film of the ring-block friction pair of the present invention can effectively prevent the transfer film generated by the friction on the surface of the ring sample from being contaminated by the cleaning fluid during the online cutting process, especially under extreme conditions such as high temperature, low speed and low load, and seawater. The structure and composition of the transfer film on the surface of the sample can still be kept intact and authentic, ensuring the accuracy of the subsequent characterization analysis results.

[0038] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A characterization and protection method for the transfer film of the ring-block friction pair, characterized in that: The steps include: During the cutting process of the ring sample (01), a circular protective tape (02) is used to protect the ring-block friction pair transfer film of the ring sample (01); the circular protective tape (02) includes a three-layer composite structure, which is a protective layer (026), a functional layer (025) and an adhesive layer in sequence; the functional layer (025) is a functional tape whose thickness and material are adjusted according to the test environment conditions; the adhesive layer includes an inner area (021) and an outer area (022); the outer area (022) is an adhesive glue, which is fixed to the end faces of both sides of the ring sample (01) through its adhesiveness; the inner area (021) is a groove area without adhesive glue in the adhesive layer, which covers the wear surface to be analyzed in the ring-block friction pair transfer film.

2. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 1 is characterized in that: The test environment conditions include seawater environment, low speed and low load, and high temperature environment.

3. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 2 is characterized in that: When the test environment is a seawater environment, the seawater concentration is divided into low concentration, medium concentration and high concentration; the low concentration simulates natural seawater, and its NaCl concentration is lower than 3.5 wt.%; the medium concentration simulates a high-salt sea area, and its NaCl concentration is 3.5 wt.%-5.0 wt.%; the high concentration simulates an extreme salt water environment, and its NaCl concentration is higher than 5.0 wt.%; the thickness of the functional layer (025) is 2.0-3.5 mm, and its material components include a resin matrix, a water absorbent and a chloride ion absorbent.

4. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 3 is characterized in that: Under low-concentration seawater conditions, the mass ratio of the resin matrix, water absorbent and chloride ion absorbent is 88-92:5:3-7; under medium-concentration seawater conditions, the mass ratio of the resin matrix, water absorbent and chloride ion absorbent is 83-87:5:8-12; under high-concentration seawater conditions, the mass ratio of the resin matrix, water absorbent and chloride ion absorbent is 78-82:5:13-17.

5. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 3 is characterized in that: The resin matrix includes one of polyurethane, epoxy resin, and polyvinylidene fluoride; the water absorbent includes one of sodium polyacrylate, polyvinyl alcohol, and cellulose derivatives; the chloride ion absorbent includes one of hydroxide-type strong base anion exchange resin, quaternary ammonium cationic adsorption resin, and zinc oxide nanoparticles.

6. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 2 is characterized in that: The test environment condition is low speed and low load, the speed of low speed and low load is 0-100 rpm, the load is 0-50 N; the thickness of the functional layer (025) is 0.5-1.5 mm.

7. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 2 is characterized in that: When the test environment is a high temperature environment, when the temperature is 150-300°C, the material of the functional layer (025) includes one of polyimide, polyetheretherketone, and phenolic resin-based composite materials; when the temperature is 300-1000°C, the material of the functional layer (025) includes one of ceramic fiber, alumina fiber, and silicon carbide fiber.

8. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 1 is characterized in that: A bending line (023) is provided at the bending portion where the outer region (022) contacts and is fixed to the end surfaces on both sides of the ring sample (01).

9. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 1 is characterized in that: Its operation process in friction testing includes the following steps: (1) Install the ring specimen and the block specimen in the fixture of the experimental device respectively, and start the friction test according to the preset friction test conditions, including speed, load, temperature and time parameters; (2) After the friction test, take out the ring sample; observe the transfer film on its worn surface and determine the area to be analyzed; the area to be analyzed is the part where the surface morphology and state after the friction test are significantly different from those of the unworn area, which is convenient for further characterization and analysis of the friction and wear mechanism; (3) Align the inner area of ​​the adhesive layer of the protective tape with the area to be analyzed of the ring sample, so that the inner area covers the wear surface to be analyzed in the transfer film of the ring-block friction pair, and the outer area adheres to the end surfaces on both sides of the ring sample to complete the fixation, preventing the protective tape from shifting during the cutting process; (4) Perform wire cutting along the outer contour of the circular protective tape. After completion, take out the small ring sample obtained by cutting, clean the residual contaminants, and dry it for further testing; (5) Before characterization testing, remove the protective tape covering the small ring specimen and then conduct characterization testing.

10. The characterization and protection method for the transfer film of the ring-block friction pair according to claim 9 is characterized in that: In the step (5), the characterization test includes scanning electron microscopy analysis, X-ray diffraction analysis, energy spectrum analysis, and X-ray photoelectron spectroscopy analysis.

Citation Information

Patent Citations

  • cut-resistant strips and method of attaching a cut-resistant strip.

    CH711947A2

  • Method for processing wafer

    CN102208366A

  • Anti-static wafer cutting film easy to pick

    CN103009758A

  • Protective film and laser cutting method

    CN106799548A

  • Processing method of concentric-square-shaped double faced adhesive tape

    CN112621888A